Ion Exchange Column Studies with Phenol: Choice of Solvent and Flow Rate - Bhat, C.V.; Vardia, Jitendra (Asian Journal of Chemistry, 2010)
The field of ion exchange has wide applications both in industryand laboratory. Most of the practical applications of ion exchangeinvolve dynamic studies. This paper describes dynamic columnstudies of phenol with resin Dowex 1 x 4 in OH- form, variationin flow rate as solvent medium both during exchange and elutionof phenol were studied to optimize the column parameters andchoice of the solvent medium.